Why Malaysia needs research universities? - Abdulsomad, Kamaruddin; Abdullah, Siti Alida John; Khalil, Samihah (2013)
The aim of this article is to address issues relating to the transformation of the Malaysian economy and the policy shift in Malaysia over the last five decades.The launching of the Third Industrial Master Plan (IMP3), 2006-2020, and the new strategy of innovation led-growth is expected to drive industrialization to a higher level of global competitiveness, through transformation and innovation of the manufacturing and services sectors.This paper argues that innovation led-growth strategy in Malaysia needs research universities as an active engine of growth.The multi-dimensional role of universities is discussed by using open innovation approach. In addition, the triple helix system of relationships between university, industry and government could be expected to enhance the relevance of universities as active agents of innovation and sustainable development.